Integrating Catholic Teachings into Education: Promoting Sustainable Practices Through Laudato Si’ in Lebanon - Nada Mallah Boustani (Religions)
Environmental challenges have become essential to study in today’s world because of the technical advancements and human achievements that have promoted an overestimation of human capabilities. This study explores the evolving relationship between humanity and nature through the lens of Catholic Church teachings, particularly the Laudato Si’ encyclical call for an “ecological conversion” (LS). It traces the historical transition from anthropocentrism to an ecological consciousness, examining theological perspectives and contemporary environmental ethics. A key focus is the role of liberation theology in shaping environmental justice. Key themes include the transition from anthropocentrism to a more comprehensive understanding of human–nature interactions, as well as the impact of liberation theology on environmental justice. Grounded in a qualitative research approach, this study investigates the potential of educational programs in Lebanon’s unique socio-cultural context to foster ethical and sustainable environmental practices. Through thematic analysis, this research highlights the concept of ecological conversion—a transformative shift in lifestyle and spirituality rooted in the principles of integral ecology. The findings show that educational initiatives based on Catholic Church teachings can successfully promote environmental stewardship and social justice. This article contributes to the discussion of environmental ethics by emphasizing the significance of an ecumenical and holistic approach, advocating for a synergy of spiritual beliefs and practical activities to confront the ecological issue. It concludes that achieving lasting environmental transformation requires collaboration, solidarity, and a collective commitment to the common good.